Influência do teor de cobre na usinabilidade da liga de alumínio 6351 - Gonçalves, Ricardo Augusto (2016)
The main purpose of this work is to study the influence of copper content on Al-Si-Mg aluminum alloy (6351) machinability. The machinability was evaluated through cutting tool torque and thrust force measurements, machined surface roughness, roundness, cilindricity and burrs formation, chip form and sub superficial modifications during drilling, reaming and tapping processes. The 6351 aluminum alloy samples were produced with five levels of copper (0.07%, 0.23%, 0.94%, 1.43% and 1.93%) with chemical composition of the other alloying elements practically constant within the recommended range by The Aluminum Association for this alloy. The main mechanical properties of the 6351 aluminum alloy samples were obtained by microstructural analysis and microhardness, hardness, tensile and impact tests. Major amounts of copper resulted in significant increase in microhardness, hardness and ultimate tensile strength of the aluminum alloy, while elongation after fracture decreased. A 23 factorial design was used to verify the effect of copper content and the cutting parameters, cutting speed and feed rate, in the machinability responses. Furthermore, an adjusted statistical model was developed to optimize the cutting parameters selection of the best copper content for each response. The results showed significant influence of copper content in machinability. Lower values of torque and thrust forces, lower roundness and cilindricity, better surface finish, besides smaller chips and burrs were obtained increasing copper content in Al-Si-Mg aluminum alloy (6351).